Managing Protected Areas People and Places - Finneran, Niall; Hewlett, Denise; Clarke, Richard (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book brings together 16 specially commissioned chapters drawn from a range of different professional-practitioner and academic global perspectives on the importance of the relationship between people and green and blue spaces. It focuses on issues surrounding the importance of natural environments on public health and wellbeing, and the environmental, cultural, and social importance of green and blue spaces that can result through responsible and sustainable adaptive management processes. It explores how the Covid-19 pandemic forced reconsiderations of our relationship with these natural spaces and highlights the important impact of the pace of climate change. While not pretending to have the answers, the stimulating and imaginative contributions embrace rich perspectives drawn from backgrounds as diverse as heritage studies, tourism, conservation, geography, policy formulation, public health, environmental health, research methods, history, literature, art, and theology. Niall Finneran is Professor of Historical Archaeology and Heritage at the University of Winchester, UK. He is the author of over 100 publications which focus on heritage, archaeology and anthropological topics focusing mainly upon the Caribbean and Africa. He is a fellow of the Society of Antiquaries of London and has directed fieldwork projects in Africa, Asia, Europe and the Americas. Denise Hewlett is Professor of Research-Knowledge Exchange at the University of Winchester, UK and is Visiting Professor at Bournemouth University, UK. She specializes in leading national and international research partnerships. Denise works with institutions including the International Union for Conservation of Nature, European Union Environmental and Research Directorates and in UK, as Trustee for National Association of Areas of Outstanding Natural Beauty (NAAONB). She is a member of the Landscape Institute, and Fellow of Royal Geographic Society. Richard N Clarke is an environmental professional, executive coach, and change management consultant with over thirty-five years of experience. He has worked with organisations, teams, and individuals to enable environmental conservation and enhancement through strategic management, policy development and organisational management. He is a Fellow of the RSA.